Why Do Indonesians Support Controversial Draft-Law? Identity, Group-Based Anger, and Collective Action - Alfiannor, Muhammad; Shadiqi, Muhammad Abdan; Zidan, Rifki (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2021)
The total number of cases of sexual abuse against women in Indonesia is increasing every year. However, there are issues with these rules because there is no specific legal framework that controls sexual violence. The students who were dissatisfied with the parliament’s performance then carried out a large demonstration that spread across various cities in Indonesia. Demonstrations are examples of collective action. According to the Social Identity Model of Collective Action (SIMCA) from [6], at least three things can trigger or predict the emergence of collective action, namely social identity, efficacy, and anger. This study uses a quantitative approach with data collection to college students across Indonesia. The data collection process is carried out by an online survey through SurveyMonkey. We collected 107 people with an age range of 17-29 years (Mage=20.33; SD=1.984). The most common age was 21 years (26%). Data was dominated by females with 93 people (87%) and males with 14 people (13%). We analyzed the data using mediation model regression with the PROCESS MACRO Hayes. The results show that group-based anger significantly mediates the effect of politicized identity on collective action. However, politicized identity and group-based anger significantly predict directly on collective action.